2016
DOI: 10.1177/1073191116641507
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Careless Responding With the Psychopathic Personality Inventory–Revised Validity Scales

Abstract: The Psychopathic Personality Inventory-Revised (PPI-R) includes validity scales that assess Deviant Responding (DR), Virtuous Responding, and Inconsistent Responding. We examined the utility of these scales for identifying careless responding using data from two online studies that examined correlates of psychopathy in college students (Sample 1: N = 583; Sample 2: N = 454). Compared with those below the cut scores, those above the cut on the DR scale yielded consistently lower validity coefficients when PPI-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The current study examined data from a college student sample because most PPI-R studies have used college student samples. Marcus, Church, O'Connell, and Lilienfeld (2016) reported that of 77 published PPI-R studies, 48 assessed college students, 15 assessed community members, and only 14 of the samples were drawn from forensic populations. Given the extant literature, an IRT study of the PPI-R in college students may be useful to researchers.…”
Section: Present Studymentioning
confidence: 99%
“…The current study examined data from a college student sample because most PPI-R studies have used college student samples. Marcus, Church, O'Connell, and Lilienfeld (2016) reported that of 77 published PPI-R studies, 48 assessed college students, 15 assessed community members, and only 14 of the samples were drawn from forensic populations. Given the extant literature, an IRT study of the PPI-R in college students may be useful to researchers.…”
Section: Present Studymentioning
confidence: 99%
“…Although validity scales designed to identify inconsistent responding are increasingly available for self‐report psychopathy measures (e.g., Kelley et al, ; Mowle et al, ; Penson et al, ), only the Psychopathic Personality Inventory‐Revised (PPI‐R; Lilienfeld & Widows, ) and Elemental Psychopathy Assessment (Lynam et al, ) originally contained indicators of positive impression management (e.g., consciously or unconsciously portraying oneself in an unrealistically favorable light; Paulhus, ). Moreover, few studies have examined the utility of these scales in detecting problematic response styles on self‐report psychopathy measures (Anderson, Sellbom, Wygant, & Edens, ; Kelley et al, ; Marcus, Church, O'Connell, & Lilienfeld, ; Nikolova, Hendry, Douglas, Edens, & Lilienfeld, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since this was not the case, one can only conclude that the VR scale was an inappropriate measure of self-deception in the current sample. Marcus et al (2018) reported that VR showed no moderating effect in the relation between the SI scale and the Triarchic Psychopathy Measure (Patrick, 2010) in an undergraduate sample. In this study, the Cronbach's alpha was higher (α = .66) than in the current sample, but still insufficient.…”
Section: Discussionmentioning
confidence: 92%